2021
DOI: 10.1016/j.isci.2021.103097
|View full text |Cite
|
Sign up to set email alerts
|

Splicing factor Srsf5 deletion disrupts alternative splicing and causes noncompaction of ventricular myocardium

Abstract: Summary The serine/arginine-rich (SR) family of splicing factors plays important roles in mRNA splicing activation, repression, export, stabilization, and translation. SR-splicing factor 5 (SRSF5) is a glucose-inducible protein that promotes tumor cell growth. However, the functional role of SRSF5 in tissue development and disease remains unknown. Here, Srsf5 knockout ( Srsf5 −/− ) mice were generated using CRISPR-Cas9. Mutant mice were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Examination of publicly available data identified several molecular partners of HP1γ that when inactivated, result in a significant increase in the splicing noise. These partners include PPL1 28 , a peptidyl prolyl isomerase-like spliceosome component, ZC3H13, a zinc finger protein recruiting RNA methyl transferases involved in N 6-adenosine methylation (m6A) modification 29 , 30 , and the Ser/Arg-rich protein SRSF5 31 (Supplementary Fig. 11 ).…”
Section: Resultsmentioning
confidence: 99%
“…Examination of publicly available data identified several molecular partners of HP1γ that when inactivated, result in a significant increase in the splicing noise. These partners include PPL1 28 , a peptidyl prolyl isomerase-like spliceosome component, ZC3H13, a zinc finger protein recruiting RNA methyl transferases involved in N 6-adenosine methylation (m6A) modification 29 , 30 , and the Ser/Arg-rich protein SRSF5 31 (Supplementary Fig. 11 ).…”
Section: Resultsmentioning
confidence: 99%
“…Essential roles of SR proteins have been reported for sex determination [ 40 , 41 ], cell differentiation [ 42 , 43 ], development of the brain [ 44 , 45 ] and heart [ 10 , 46 , 47 ], the immune system [ 48 , 49 ], and many types of cancer [ 12 , 50 , 51 ]. Here, we focus on the known functional mechanisms of SR proteins, and discuss the importance of these functions in various cancers.…”
Section: Functional Mechanisms Of Sr Proteins In Cancermentioning
confidence: 99%
“… 21 HnRNP A1 + /− mice exhibited disrupted blood pressure and heart rates. 22 Animal models have demonstrated that the absence of SRSF1, 23 SRSF5, 24 SRSF10, 25 hnRNP U 26 or hnRNP L 27 , 28 phenocopy human cardiovascular diseases such as atrial septal defects, heart failure, noncompaction of the ventricular myocardium and diabetic heart.
Fig.
…”
Section: Splicing Factors and Cardiovascular Diseasementioning
confidence: 99%
“… Splicing factors Example of genes regulated by splicing factors through AS Study source Related cardiac phenotypes Related cardiac diseases References SF3B1 Khk-C Mice Diastolic dysfunction Cardiac hypertrophy 44 SRSF1 Camk2d Mice Cardiac remodelling and fibrosis; fuzzy Z-lines and shortened sarcomeres; hypercontraction; disrupted calcium handling. DCM 23 SRSF3 mTOR Mice Systolic dysfunction; Heart failure 21 SRSF5 Myomesin Mice Noncompaction of the ventricular myocardium; increased left ventricular internal diameter and volume; irregular electrocardiogram cardiomyopathy with noncompaction of the ventricular myocardium 24 SRSF10 Triadin Mice Atrial septal defects; ventricular septal defects; thinner myocardium; atrioventricular canal defect; disrupted calcium handling 25 HnRNP A1 Mef2c, Lrrfip1, Usp28 and Abcc9 Mice Increased systolic pressures; increased heart rates; increased RR interval, PR interval and P duration DCM 22 HnRNP U Titin and Camk2d Mice Aberrant cardiomyocyte arrangement; dramatic increase of left ventricular anterior-to-posterior wall diameter; decreased fractional shortening; abnormal calcium handling activities. Heart failure 26 HnRNP L CLIP1, MED23, Tmem184b , and CaV1.2 Mice; humans; rats Reduced sensitivity of CaV1.2 channels to nifedipine.…”
Section: Splicing Factors and Cardiovascular Diseasementioning
confidence: 99%